Design and evaluation of peptide-18-targeted nanoliposomes constructed by poly(2-oxazoline)-DOPE for doxorubicin delivery. (4th July 2021) - Devrim, Burcu; Bolat, Zeynep Busra; Telci, Dilek; Şahin, Fikrettin; Gulyuz, Sevgi; Ozkose, Umut Ugur; Yilmaz, Ozgur; Bozkır, Asuman
Abstract: Aims: The aim of this study is to develop targeted nanoliposome formulations to provide efficient treatment for breast cancer. In this study, peptide 18-modified poly(2-ethyl-2-oxazoline)-dioleoylphosphatidylethanolamine (P18-PEtOx-DOPE), was synthesised to construct nanoliposomes. Methods: Doxorubicin (DOX) was encapsulated into the nanoliposomes by ethanol injection method. Particle size and polydispersity index were measured by dynamic light scattering. Zeta potential was determined by electrophoretic laser Doppler anemometry. The shape of the nanoliposomes was examined by transmission electron microscope. Specific bindings of P18-PEtOx-DOPE nanoliposomes were demonstrated on AU565 cells by confocal microscopy and flow cytometry studies. Results: DOX-loaded nanoliposomes with particle diameter of 150.00 ± 2.84 nm and PDI of 0.212 ± 0.013 were obtained. PEtOx-DOPE and PEtOx-DOPE nanoliposomes are non-toxic on HUVEC, HEK293 and hMSC cells for 48 h. Furthermore, P18-PEtOx-DOPE nanoliposomes demonstrated specificity towards AU565 cells with high binding affinity. Conclusions: As a result, DOX-loaded P18-PEtOx-DOPE nanoliposomes can serve as favourable candidates in breast cancer targeted therapy.